Analisis Kelayakan Usaha Perikanan Pukat Cincin Pada KM. Asia Jaya 03 - Rasdam Rasdam; Resky Amalia Rajab; Silmen Dima Rohi (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2021)
The purpose of this research was to determine the necessary costs, benefits and feasibility of fishing effort on purse seiner refrigerated frezzer. This research uses descriptive method, sampling with purposive sampling and financial analysis. Business analysis is carried out by identifying the costs incurred in the form of a total cost of IDR 1,362,779,900 / trip, consisting of fixed costs of IDR. 214,500,000 / trip and variable costs of IDR. 1,148,279,900. Income from the sale of the catch is IDR. 2,974,282,400 / trip with a net profit of IDR. 1,611,502,500 and for the ship owner gets a share of 60% so that in 1 fishing trip he gets a profit of IDR.. 966,901,500. It takes 6 trips (3 years) of fishing operations with a profit of IDR. 1,611,502,500 / trip to reach the break even point. The B / C ratio value of 2.18 is greater than 1, so the fishing business by KM. Asia Jaya 03 with purse seine fishing gear is declared feasible to operate and continue.